ENGLISH LANGUAGE TEACHING BASED ON MERDEKA CURRICULUM IN PUBLIC SENIOR HIGH SCHOOL LEVEL IN BANDUNG: BASED ON THE SITUATIONAL ANALYSIS - Lukman Arif Rachman (IKIP Siliwangi, 2023)
The Merdeka Curriculum has been implemented in all public senior high school levels in Bandung, however, this has led to some interpretations from teachers that have an impact on how the teaching and learning process is carried out in the classroom, particularly when it comes to teaching English. However, various factors, such as student, institution, and social issues, have an impact on how English language teaching is implemented. As a result, the study examined how the Merdeka Curriculum was implemented in English language instruction at the senior high school level in Bandung's public schools. The study's objectives are to shed light on how English language teaching is being implemented in senior high schools in Bandung and to identify the variables that influence the various ways in which it is being done. The data was gathered by observing English teachers and students in two different public schools in Bandung and interviewing them. The study's findings indicate that varied emphasis was placed on how teachers planned lessons, carried out the teaching and learning process, and evaluated students. varied characteristics of the teachers and students, as well as varied conditions in the school and society, have an impact on the diverse implementation.